Knowledge and Management Practices of Paediatricians about Autism Spectrum Disorder in Kathmandu, Nepal - Khatri, Goma Kumari; Onta, Sharad Raj; Tiwari, Suresh; Choulagai, BP (Journal of Nepal Paediatric Society, 2011)
Introduction: Autism Spectrum Disorder is increasing day by day around the world. Recent finding of CDC shows that this problem occurs 1 in 110 populations. This problem is such a disorder, which not only affects to the individuals but also the families, society and nation as a whole if not managed properly. Aim: The aim of this study was to assess the knowledge and management practices of Paediatricians about Autism Spectrum Disorder. Methods: The study design was descriptive and cross sectional. A census was used to select the study unit and self-administered questionnaire was used to collect data. Results: Out of 54 Paediatricians, 64.8 percent had inadequet knowledge and 59.3 percent had inadequet practice related to Autism Spectrum Disorder. Majority of them (79.6%) knew that Autism Spectrum Disorder is a Developmental Disorder but they (24.1%) also mentioned it to be mental retardation and 13 percent thought that it as a form of psychosis. Most of Paediatricians, (72.2%) knew that Autism Spectrum Disorder could be due to genetic reason. However, a significant number of respondents 22.2 percent also believed that Autism Spectrum Disorder could occur due to the neglect of children. Almost fifty percent of Paediatricians had rarely handled the Autistic child and a majority of the Paediatricians, (90.7%) found it difficult to diagnose this disease. Conclusion: Most of the Paediatricians in Nepal have inadequet knowledge and practice related to Autism Spectrum Disorder. Although some of the practice was good, they also had misconceptions as to managing the children with Autistic disorders. Most of the Paediatricians need to improve their knowledge and practice related to Autism Spectrum Disorder. Key words: Autism Spectrum Disorder (ASD); Autistic; socialisation problem; communication problem; steriotyped behavior. DOI: 10.3126/jnps.v31i2.4640 J Nep Paedtr Soc 2010;31(2):98-104